2020
DOI: 10.1371/journal.pone.0237092
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning for cerebral angiography segmentation from non-contrast computed tomography

Abstract: Cerebral computed tomography angiography is a widely available imaging technique that helps in the diagnosis of vascular pathologies. Contrast administration is needed to accurately assess the arteries. On non-contrast computed tomography, arteries are hardly distinguishable from the brain tissue, therefore, radiologists do not consider this imaging modality appropriate for the evaluation of vascular pathologies. There are known contraindications to administering iodinated contrast media, and in these cases, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…As suggested by its name, TOF MRA relies on a principle known as flow-related enhancement, which happens when completely magnetised blood flows into a slab of magnetically saturated tissue whose signal has been muted by repeated RF-pulses 27 . However, the long acquisition time and high operational costs make it difficult to employ for cerebral artery visualisation 28,29 . Furthermore, MRA has been shown to overestimate stenosis compared to other modalities 30 .…”
Section: Modalities For 3d Vascular Imagingmentioning
confidence: 99%
“…As suggested by its name, TOF MRA relies on a principle known as flow-related enhancement, which happens when completely magnetised blood flows into a slab of magnetically saturated tissue whose signal has been muted by repeated RF-pulses 27 . However, the long acquisition time and high operational costs make it difficult to employ for cerebral artery visualisation 28,29 . Furthermore, MRA has been shown to overestimate stenosis compared to other modalities 30 .…”
Section: Modalities For 3d Vascular Imagingmentioning
confidence: 99%
“…Deep learning systems can facilitate patient triage and improve clinical efficiency. O'Neill et al developed a model to detect ICH on NCCTB and showed that using this system as a triage tool reduced image interpretation turnaround times [52] [44]. Poirot et al applied deep learning to improve dual-energy CT (DECT) scan processing.…”
Section: The Current State Of Machine Learning Applied To Ctb Datamentioning
confidence: 99%
“…Deep learning (DL) has shown significant potential in medical image analysis tasks. Notably, the U-Net framework with symmetric network architecture is widely adopted in the field of medical image segmentation because of its flexibility and achieves remarkable successes ( Jin et al, 2020 ; Klimont et al, 2020 ; Mubashar et al, 2022 ). Previous models have focused on the segmentation of the specific artery (e.g., the carotid artery) or the whole 3D cerebral vessels ( Groves et al, 2020 ; Klimont et al, 2020 ; Bortsova et al, 2021 ; Guo et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the U-Net framework with symmetric network architecture is widely adopted in the field of medical image segmentation because of its flexibility and achieves remarkable successes ( Jin et al, 2020 ; Klimont et al, 2020 ; Mubashar et al, 2022 ). Previous models have focused on the segmentation of the specific artery (e.g., the carotid artery) or the whole 3D cerebral vessels ( Groves et al, 2020 ; Klimont et al, 2020 ; Bortsova et al, 2021 ; Guo et al, 2021 ). Only few studies strive for the automatic segmentation or labeling of intracranial arteries involved with detailed segments (i.e., automatic labelling of fine segments).…”
Section: Introductionmentioning
confidence: 99%